Analysis and Optimization of Betanin Extraction from Juice of the Peel and Fleshes of Red Dragon Fruit (Hylocereus costaricencis) - Kania, Prina Puspa; Furqon, Ayi (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2024)
Currently, health issues are no longer related to how to treat diseases but rather prioritize the prevention of various diseases by eating foods that contain high levels of nutrients, known as functional foods. Red dragon fruit contains betanin dye, which has various health benefits and can be grouped into functional foods. Some studies have been conducted to obtain betanin from red dragon fruit, but it is not yet known how much betanin content is present in the juice of the flesh and peel of red dragon fruit (Hylocereus costaricencis) and how to determine the optimum extraction conditions. This study aims to analyze the betanin content in the skin and flesh of red dragon fruit and the optimal extraction conditions so that betanin can be obtained in maximum quantities. The extraction method used was the maceration method with three solvents, namely, water, ethanol, and methanol. Analysis of the betanin content in the skin and flesh of dragon fruit was carried out using UV‒Vis spectrophotometry. The results of the study revealed that water solvents can extract betanin well. In addition, the ratios of dragon fruit to water were 2:1 (flesh and water) and 1:1 (skin and water), respectively, while the optimum extraction temperature was 4–8°C. The optimum extraction time was 24 hours. Betanin was obtained from the skin and flesh of red dragon fruit at a sample:solvent ratio of 1:1, with values of 21.71 mg/mL and 17.8 mg/mL, respectively.